Performance evaluation of constant frequency torque controller-based and SVM-based of direct torque control of induction motor drives - Ahmad, Md Zarafi (2007)
Direct torque control is a control technique used in AC drive system to obtain high performance torque control. The conventional DTC drive contains a pair of hysteresis comparators, a flux and torque estimator and voltage look-up table. The torque and flux are controlled simultaneously by applying suitable voltage vectors, and limiting these quantities within their hytaresis band. At the same time, de-coupled control of torque and flux were achieved. However, the DTC drives utilizing hysteresis comparators suffer from high torque ripple and variable switching frequency. The most common solution to this problem is to use the space vector based which depends on the reference torque and flux. The reference voltage vector is then realized using a voltage space vector modulator (SVM). Nevertheless, by applying this method, the basic structure of DTC is lost and needs for high performance of processor. On the other hand, constant frequency torque controller also has managed to solve the problem. The proposed controller has retained the basic structure of DTC drive as in hysteresis-based. This paper present the comparison and evaluation of the performances of those techniques of DTC drive that applied to induction machine through simulation using MATLAB/SIMULINK. The evaluation was made based on the drive performances, which include dynamic torque, feasibility, and the complexity of the system. The results obtained showed that the constant frequency torque controllerbased gives better performance in terms of dynamic torque and at the same time retain the simple structure of DTC drive system.